Damage evolution of coated steel pipe under cathodic-protection in soil. Issue 1 (3rd January 2017) - Li, Ximing; Castaneda, Homero
Abstract : Purpose: The purpose of this paper is to study the damage evolution (DE) of coated API5L-X52 steel pipe with cathodic protection (CP) in nature soil. Also, different coating conditions, intact coating and coating with artificial holiday defect are considered to study the electrochemical behavior combined with soil properties and CP potential. An approach of electrochemical impedance spectroscopy (EIS) analysis is also developed. Design/methodology/approach: This work developed a laboratory experimental set-up of coated pipeline under CP in nature soil. The electrochemical behavior has been investigated using EIS. The CP potential provided by a DC power supplier has been adjusted and recorded to maintain the protective potential of pipe at −850 mV vs Cu/CuSO4 . Findings: Various parameters were derived from the EIS fitting data by equivalent circuit models to illustrate the three DE stages of coated carbon steel in soil. Each stage changes faster for the artificial defect coating system compared to intact coating, especially at the initial water uptake and ion transport stage. The CP potential has been proved to be correlated to the soil properties, coating conditions and DE stages of pipeline samples. Originality/value: This work is the first one to study DE of coated pipeline system under CP in soil. It introduces an electrochemical method to study coating defects which can promote to design the deterministic model to detect coating defects of buried pipe using AC impedance technique.